Perancangan Sistem Informasi Mobile Pada Ujian Program Studi Manajemen Informatika AMIK Boekittinggi - nori sahrun (Prodi Sistem Informasi FST Universitas Jambi, 2022)
Implementation of conventional exams is still applied in the Information Management Study Program of AMIK Boekittinggi where every daily test, quiz, midterm exam or final semester examines paper and examination of the results of examinations conducted by lecturers who teach courses takes a long time and acts of cheating that occur in the examination process. In one examination period, the AMIK Boekittinggi Informatics Management Study Program requires more than 5 reams of paper for the examination. This is not efficient, because the procurement of paper requires a lot of money and time. The solution to this problem is to hold an exam via a mobile device. The use of mobile devices as a medium for conducting exams will reduce costs, because all that is needed is a mobile device for all types of exams. Meanwhile, for exam management using a web application. This study aims to build a Test Management Information System for the AMIK Boekittinggi Information System. The research method used in this study adopted the waterfall system development. The stages of the waterfall method include requirements definitions, system and software design, implementation, and system testing. The programming languages ​​used are Java, PHP and MYSQL as the database. The implementation of this information system includes exam management, exam question management and data management for lecturers and students which will produce a score output. The results of this study have built an examination management information system as a solution to using paper, minimizing time in examination examinations and fraud in the implementation of exams.